Evaluation of otolith shape analysis as a tool for discriminating adults of Baltic cod stocks. (20th January 2013) - Paul, K.; Oeberst, R.; Hammer, C.
Summary The two stocks of cod (Gadus morhua L.) in the Baltic Sea are separated by two main spawning areas and main spawning periods. Migrations of juveniles and adults result in the mixing of both stocks. At present, the two stocks have been discriminated using inter alia meristics and morphometry, genetics and tagging experiments. However, using these techniques it is not possible to assign single, non‐spawning individuals to a certain stock. Since otolith shape analysis has become a common method for stock discrimination and has been applied successfully to several Atlantic cod stocks, it was applied here for the Baltic cod stocks. To obtain baseline samples, spawning cod were sampled between 2005 and 2009 in the main spawning areas during the spawning periods. The otolith contours were digitized and elliptical Fourier descriptors were analyzed. Both stocks differed significantly in their otolith shapes, and individuals could be allocated with >90% accuracy to one of the stocks. Both Baltic cod stocks and cod from West Greenland were discriminated with 93% correct classification. These results highlight otolith shape analysis as a useful tool to discriminate adults of Baltic cod stocks.